2013
DOI: 10.1177/1545968312474118
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Split-Belt Treadmill Training Improves Poststroke Step Length Asymmetry

Abstract: Background and objective Previous studies suggest that error augmentation may be used as a strategy to achieve longer-term changes in gait deficits after stroke. The purpose of this study was to determine whether longer-term improvements in step length asymmetry could be achieved with repeated split-belt treadmill walking practice using an error augmentation strategy. Methods 13 persons with chronic stroke (>6 months) participated in testing: (1) prior to 12 sessions of split-belt treadmill training, (2) aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
287
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 249 publications
(306 citation statements)
references
References 41 publications
17
287
2
Order By: Relevance
“…Spatial symmetry has been shown to improve with various types of gait training, such as body weight supported treadmill training, split belt treadmill training, rhythmic facilitation, and traditional physical therapy such as neurodevelopmental treatment (i.e. NDT) (Hassid et al, 1997;Thaut et al, 1997;Patterson et al, 2010;Reisman et al, 2013). Some studies have shown temporary improvements in temporal and kinetic symmetry (Hassid et al, 1997;Reisman et al, 2007), however, others show temporal symmetry remains unchanged after treadmill training or traditional gait rehabilitation (Silver et al, 2000;Den Otter et al, 2006;Reisman et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…Spatial symmetry has been shown to improve with various types of gait training, such as body weight supported treadmill training, split belt treadmill training, rhythmic facilitation, and traditional physical therapy such as neurodevelopmental treatment (i.e. NDT) (Hassid et al, 1997;Thaut et al, 1997;Patterson et al, 2010;Reisman et al, 2013). Some studies have shown temporary improvements in temporal and kinetic symmetry (Hassid et al, 1997;Reisman et al, 2007), however, others show temporal symmetry remains unchanged after treadmill training or traditional gait rehabilitation (Silver et al, 2000;Den Otter et al, 2006;Reisman et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, adults show this faster re-learning even if the adapted pattern has been "washed-out" or unlearned, demonstrating memory of a different version of the same motor skill (Huang et al 2011;Malone et al 2011). This faster re-learning is important not only for successful movement in everyday life, but it can also facilitate motor learning in rehabilitation (Reisman et al 2013).…”
mentioning
confidence: 99%
“…Furthermore, a relatively short training period can cause large changes in coordination: for example, hemiparetic individuals with an average step length asymmetry of 0.15m improved this to <0.05m immediately following 15 minutes of split-belt walkingroughly a 67% improvement in symmetry [35]. Improvements reported over the course of a four-week split-belt training study were not as large (~32% change in step length symmetry from pre-to post-training), but these were retained nearly 100% for upwards of 3 months post-training [40].…”
Section: Gait Training To Alter Interlimb Coordinationmentioning
confidence: 73%
“…In their long-term training study, Reisman et al [40] found that while split-belt training improved step length symmetry, there was no concurrent change in preferred walking speed. Although Kahn and Hornby [24] found improvements in preferred gait speed following unilateral stepping training, there was no correlation between these gains and improvements in step length symmetry.…”
Section: Gait Training To Alter Interlimb Coordinationmentioning
confidence: 97%
See 1 more Smart Citation